ZnNixMnxCo2–2xO4 Spinel as a High‐Voltage and High‐Capacity Cathode Material for Nonaqueous Zn‐Ion Batteries. Issue 22 (16th May 2018) - Pan, Chengsi; Zhang, Ruixian; Nuzzo, Ralph G.; Gewirth, Andrew A.
Abstract: Nonaqueous Zn‐ion batteries are regarded as one alternative for Li‐ion batteries. Such batteries not only afford attractive attributes of cost, but also embody the advantages of the high‐specific capacities of Zn anodes, as well as the wide potential window of nonaqueous electrolytes. To fully exploit these advantages, improved cathode materials are highly desired. In this manuscript, a new series of spinels, ZnNi x Mn x Co2–2 x O4, are reported as cathode materials for nonaqueous Zn‐ion batteries. Full cells constructed using this new spinel ( x = 1/2) as a cathode paired with a metal anode showed capacities over 200 cycles of 174 mAh g −1 and an open circuit potential of 2.05 V. The battery exhibits an energy density of 305 Wh kg −1, which is the highest energy density yet reported for a Zn‐intercalation cathode. The data show that the Zn 2+ ions reversibly intercalate into the spinel structure during the charge/discharge processes, a compositional transformation directly correlated with a multiply reversible conversion between Co 4+ /Co 3+, Ni 4+ /Ni 3+ /Ni 2+, and Mn 4+ /Mn 3+ oxidation states within the lattice. The data suggest that Mn, Ni cosubstitution for Co in ZnCo2 O4 is an efficient method to facilitate Zn‐deintercalation and enhance discharge capacity, which may provide some guidelines for designing more attractive multivalent cathodes materials. Abstract : ZnNi x Mn x Co2–2 x O4 spinels are reported as high‐voltage and high‐capacity cathode materials for nonaqueous rechargeable Zn‐ion batteries. Full coin cells constructed using this new spinel show capacities over 200 cycles of 174 mAh g −1 . The energy density reaches up to 305 Wh kg −1 which is the highest power density yet reported for a nonaqueous Zn‐ion battery system.